Analysis of Pressure Effects for Current Density and Electric Field Performance of Gas Insulations - M. Jamail, N. A.; M. Hisham, M. A. N.; Kamarudin, M. S.; M. Yousof, M. F.; Kamarudin, Q. E.; M. Piah, M. A.; M. Jamail, N. S. (International Journal of Integrated Engineering, 2020)
Gas insulation had been used widely in high voltage industry as a dielectric component. According to the arrangement of gas particles that far apart from each other, lead to the movement of gas particles react fast with high temperature and pressure. Hence when breakdown occurred in a system, it will quickly protect the system by diminished the sparks to avoid flashover occurred. The intention of this research is to determine relationship between current density and electric field of gas insulations that have been used in the insulator. HV experimental test has been conducted, to obtain breakdown voltage of air to use as applied voltage in the simulation for breakdown purpose of three insulation gasses, which are Sulphur Hexafluoride (SF6), Octafluoropropane (C3F8), and Nitrogen (N2). Physical properties such as thermal conductivity, electrical conductivity, and temperature of each gasses are require to identify value of current density and electric field of each insulation gasses. Furthermore, two pressure spots were placed symmetrically between two electrodes in the insulator. Based on simulation’s results, C3F8 is the best gas insulation because in normal condition and when presence of pressures it had lowest current density compared to SF6 and N2. Thus, C3F8 had the highest value of electric field among the insulation gasses. Electrical insulator is an internal electrical charger that cannot move freely and its contrast with semiconductors and conductors that can conduct electrical current easily. When the insulating material was used to avoid electrical discharges, it’s called insulation. High voltage insulation has been used widely in industry at electrical equipment such as switchgear and circuit breaker. The importance of applied high voltage in the electrical equipment is to prevent it from damage when faulty or breakdown occurs. From the results that have been obtained, the best gas insulation can be applied in the insulator as a protective component in electrical industry.